Assessing the Impact of Interannual Climate Variability on New York City's Reservoir System - Riley, Mary Elizabeth (2006)
New York City's reservoir system supplies about nine million residents with approximately 1.3 billion gallons of water each day. Such dependence on the system requires a thorough understanding of the natural controls of its variability, as well as that of regional streamflow and precipitation. Prior studies suggest that climate variability in the Northeast depends upon large-scale northern hemisphere atmospheric and oceanic circulation patterns. In this study, the impact of large-scale climate variability on New York's reservoir system and whether interdecadal climate variations alter the influence of shorter interannual climate modes on water availability is examined. Also of importance is the interaction between these atmospheric oscillations and how these relationships might change during the different climatic regimes. Explored in this study are the influences of the Pacific Decadal Oscillation (PDO), El Nino-Southern Oscillation (ENSO), Pacific-North American Oscillation (PNA), North Atlantic Oscillation (NAO), and Atlantic Multidecadal Oscillation (AMO) on precipitation and hydrology in New York City's watershed. The direct impact of the large-scale oscillations on the quantity of water in New York's seven-reservoir system is also investigated. Statistical analysis has been performed on the data for 1951-2004, during which all data sets were available and, separately, for positive and negative PDO phases (1977-97 and 1951-76/1998-2004, respectively). The interactions between hydrological/meteorological factors and the reservoir system levels in the separate phases have also been examined. Statistically significant differences in most interactions have been found between the separate PDO phases. The results of this study indicate that the potential for predicting reservoir behavior exists. Although statistically significant, the relationships are not well enough understood to prescribe using this information for watershed management at this point. However, the study results do warrant further exploration of ...